The Role of Teachers in Fostering Empathy in Students at SD Muhammadiyah Insan Kreatif Kembaran - Titi Mulia Kinasih; Fitriah M. Suud (Yayasan Pendidikan Bima Berilmu, 2026)
This research aims to describe the role of PAI teachers in fostering students' empathetic attitudes at SD Muhammadiyah Insan Kreatif Kembaran. The research uses a qualitative approach with a case study design. The research informants consist of one PAI teacher, one principal, and five fifth-grade students selected thru purposive sampling technique. Data were collected through semi-structured interviews and analyzed using the Miles and Huberman interactive analysis model. The research results show that PAI teachers play the role of facilitators, guides, motivators, demonstrators, mediators, and learning resources in the development of students' empathy. The strategies used include role-playing, Project-Based Learning (PjBL), discussions, storytelling, social habituation, and collaboration with parents. Storytelling has been found to be the most effective strategy in helping students understand the feelings and perspectives of others because it provides a more reflective and meaningful learning experience. The development of empathy faces challenges such as the diversity of student characteristics, differences in family backgrounds, and the dynamics of classroom management. Overall, the development of empathy requires a holistic approach through the synergy of learning, school culture, and family support to support students' social-emotional development optimally.